Influence of the vector interaction and an external magnetic field on the isentropes near the chiral critical end point - Costa, Pedro (2016)
The location of the critical end point (CEP) and the isentropic trajectories in the QCD phase diagram are investigated. We use the (2+1) Nambu$-$Jona-Lasinio model with the Polyakov loop coupling for different scenarios, namely by imposing zero strange quark density, which is the case in the ultra relativistic heavy-ion collisions, and $β$-equilibrium. The influence of strong magnetic fields and of the vector interaction on the isentropic trajectories around the CEP is discussed. It is shown that the vector interaction and the magnetic field, having opposite effects on the first-order transition, affect the isentropic trajectories differently: as the vector interaction increases, the first-order transition becomes weaker and the isentropes become smoother; when a strong magnetic field is considered, the first-order transition is strengthened and the isentropes are pushed to higher temperatures. No focusing of isentropes in region towards the CEP is seen.